EFFECT OF TREATMENT ON GERMINATION OF SEEDS OF LAURUS NOBILIS L NATURAL STANDS IN LATAKIA (KASSAB) AND HAMA (ALGHAB). - الابراهيم دلال; حسن علاء الدين; محمد منهل الزعبي (Latakia University Journal -Biological Sciences Series, 2023)
This research carried out in during (2018 -2019) in Latakia (kassab) and Hama (AL ghab) Research carried out in (2018-2019) in two different geographical areas and climatic in Latakia (kassab) and Hama(ALghab). Laurus nobilis, L of fruits were collected from forest stands in the fall of (2018) Experiment was applied using (1296) seeds which were divided into five groups at fallows: (1)Control, (2) cold stratified at +4 degrees for (25-50) days,(3) Scarification mechanical,(4) Seeds without pericarp and epicarp , (5) Treatment of GA3 (1000 - 3000) ppm Study showed as follow: Treatment seed without pericarp and epicarp to surpass of rest treatments with rate (81.48-88.88)% while in treatment of GA3 (1000-3000)ppm germination increased from (77.77)% to (70.37)% due to increasing acid concentration and can play a negative role in stimulating pulp on germination. Percentage or germination increased from (14.8)% in Scarification mechanical to (88.88)% of treatment ( Seeds without pericarp and epicarp, Results suggested that seed dormancy was mainly due to pericarp and epicarp perhaps inhibitors linked to seed coat.